2017
DOI: 10.12681/jhvms.15503
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility of Enterococcus spp. isolated from freshwater fish and personnel and equipment of fish markets in northern Greece

Abstract: In total, 270 samples from freshwater fish and personnel and equipment from retail fish markets in three cities in northern Greece, were examined for presence of antimicrobial resistance and biogenic amine production of Enterococcus spp. strains. Enterococci were isolated from 9.6% of the samples; from 7.4% and 2.2%, respectively, Enterococcus faecium and Enterococcus casseliflavus were recovered. Isolates were tested for antibacterial susceptibility to 20 antibiotics used regularly in Greek hospitals. All iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…As well , the obtained results were in agreement with those displayed in Bangladesh by Rahman et al [40] who detected Enterococcus isolates from fresh water fish, exhibiting resistance to ampicillin and erythromycin, however, these isolates revealed variable levels of susceptibility to gentamycin and vancomycin. Moreover, in corroboration with the present study, Sergelidis et al [41] [44], which was done on marine water fish in Tunisia.…”
Section: Disscussionsupporting
confidence: 92%
“…As well , the obtained results were in agreement with those displayed in Bangladesh by Rahman et al [40] who detected Enterococcus isolates from fresh water fish, exhibiting resistance to ampicillin and erythromycin, however, these isolates revealed variable levels of susceptibility to gentamycin and vancomycin. Moreover, in corroboration with the present study, Sergelidis et al [41] [44], which was done on marine water fish in Tunisia.…”
Section: Disscussionsupporting
confidence: 92%
“…Sergelidis et al. (2013) stated that Enterococcus isolates of fish and fish market samples harbored the high resistance rate towards cephalosporins, penicillins, and erythromycin antimicrobial agents. Karimian et al.…”
Section: Discussionmentioning
confidence: 99%
“…Irregular and unauthorized prescription of antimicrobial agents is the probable reason for the high resistance rate.As some isolates harbored a high resistance towards human-based antimicrobial agents (those are basically used to treat human infectious diseases), it can be indirectly concluded that these isolates originated from infected staffs of seafood sales and processing centres(Ranjbar et al, 2019). The high resistance rate of E. faecalis strains isolated from food samples towards oxacillin, tetracycline, erythromycin, cefoxitin, cefazolin, trimethoprim-sulfamethoxazole, rifampin, clindamycin, and gentamicin antimicrobial agents was reported from Switzerland(Boss et al, 2016), Turkey(Sanlibaba et al, 2018), Slo-F I G U R E 2 Polymerase chain reaction (PCR) gel electrophoresis of E. faecalis isolates in the RAPD analysis vakia(Kročko et al, 2011), Africa(Olawale et al, 2015), Poland(Cybulska & Krzyśko-ŁUpicka, 2020), and South Korea(Kim et al, 2021) Sergelidis et al (2013). stated that Enterococcus isolates of fish and fish market samples harbored the high resistance rate towards cephalosporins, penicillins, and erythromycin antimicrobial agents.…”
mentioning
confidence: 99%
“…The result of biochemical identification applied by Automated identification and antibiotic sensitivity testing of suspected isolates showed two subspecies of Enterococci: E. faecium and E. faecalis. Sergelidis et al (15) were identified their isolates depending on biochemical characterization by semi-automated system WIDER (Francisco Soria Melguizo, Madrid, Spain) using the Gram positive minimal inhibitory concentration/identification panels, which was nearby method to that used in our experiment. Also, Arumugam et al (1) documented biochemical characterization of E. faecalis included Gram strain, catalase test, and growth at 6.5% NaCl/ 45°C, using Rapid HiStrepTM biochemical test kit specific for Streptococcus species.…”
Section: Discussionmentioning
confidence: 99%
“…Several Enterococcus species have been implicated in disease outbreaks in aquaculture facilities worldwide, including Egypt (11,12,13). E. faecium and E. faecalis are the most frequently encountered enterococcal species (14,15).…”
Section: Introductionmentioning
confidence: 99%